Implications of Dynamics of Land Use Shifts in Rajasthan - Sharma, Latika (Annals of Arid Zone, 2016)
Land use pattern of an area effect vegetation, land quality, local weather and quality of life. Within the interwoven fabric of time scale and spatial variability selected characteristics of land use pattern may serve as indicators and regulators of forces set into motion by human actions. From the simple clearing of trees to the accelerated conversion of fallow land into ‘barren’ the balance of natural system is impacted. It is very important to understand the land use pattern of any area and the dynamics of its shift overtime. This determines the ensuing per unit load on agriculture land, forest land, periphery areas to cities and factors responsible for land degradation. With the total geographical area of 3.42 lakh hectare, Rajasthan is largest state in the country. The state is highly diversified in terms of agro-climatic features. The Aravalli range of hills which starts from the south-west and spread upto north-east divide the state into two distinct geographical regions. The west of Aravalli is desert with arid and hyper arid situation. The major area of eastern part is semiarid and the remaining humid and sub-humid. Of the total population of 56.51 million in Rajasthan, 76.61% live in rural areas. There are 7.05 million rural households with 6.1 persons per household in the state whose main stay of life is agriculture and allied activities. Thus the pressure of population on land based activities is considerably high in the state. The study attempts to examine the shifts in the land use in Rajasthan and its implication on agriculture and ecology. The study is based on the data pertaining to 1990 to 2005. The results showed that permanent pastures and grazing lands and miscellaneous trees and grooves are declining having serious unfavorable implications for the ecology of Rajasthan. The land use dynamics show substantial shifts in the land use pattern towards non-agricultural sector. The shift is mainly from the culturable waste land part of agriculture sector and undesirable part of ecological sector. The forest area in Rajasthan is increasing at a meager rate of 0.96% per annum and at us still 7.8% of total geographical area. This is well below the required 9.0% norm for forest area decided by the government. Thus the growth in forest area by increasing the rate of forestation is very important to maintain the ecological stability. This is also necessary to maintain a balance with the ecological hazards generated by fast growing non-agriculture sector. The tendency of rapid growth of non-agriculture sector should be more on conservative terms before a sizeable portion of land mass gets blocked under non-agricultural uses.